2017
DOI: 10.1038/s41598-017-03418-0
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ augmentation ameliorates acute pancreatitis through regulation of inflammasome signalling

Abstract: Acute pancreatitis (AP) is a complicated disease without specific drug therapy. The cofactor nicotinamide adenine dinucleotide (NAD+) is an important regulator of cellular metabolism and homeostasis. However, it remains unclear whether modulation of NAD+ levels has an impact on caerulein-induced AP. Therefore, in this study, we investigated the effect of increased cellular NAD+ levels on caerulein-induced AP. We demonstrated for the first time that the activities and expression of SIRT1 were suppressed by redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…Guarente, 2013]. Overall, our findings are in agreement with the role of CYB5R3 and NQO1 as efficient intracellular generators of NAD + for utilization by sirtuins (Ross & Siegel, 2017; Shen et al., 2017), and are consistent with the notion that modulation of SIRT1 and NAD + levels represents a promising approach for the treatment of age‐associated metabolic diseases (Herranz et al., 2010; Imai, 2010; Verdin, 2015). …”
Section: Discussionsupporting
confidence: 88%
“…Guarente, 2013]. Overall, our findings are in agreement with the role of CYB5R3 and NQO1 as efficient intracellular generators of NAD + for utilization by sirtuins (Ross & Siegel, 2017; Shen et al., 2017), and are consistent with the notion that modulation of SIRT1 and NAD + levels represents a promising approach for the treatment of age‐associated metabolic diseases (Herranz et al., 2010; Imai, 2010; Verdin, 2015). …”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the ROS/NF-κB signaling pathway plays an important role in the activation of the NLRP3 inflammasome. For the NF-κB signaling pathway in the NLRP3 inflammasome, most researchers found that Acetyl-NF-κB p65 (Lys310) was upregulated and the NF-κB signaling pathway was activated, and ultimately activated the NLRP3 inflammasome [74][75][76][77]. Therefore, the Acetyl-NF-κB p65 (Lys310) antibody, which recognizes the overexpressed levels of the NF-κB p65 protein acetylated at Lys310, was also used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NF-κB activity is regulated via post-translational modifications, namely phosphorylation and acetylation. Current studies have suggested that the incapability of reduced SIRT1 activity to deacetylate the NF-κB subunit p65 at lysine-310 aggravates the inflammatory mediators [12,17,28]. Interestingly, the level of acetylated NF-κB p65 was strongly increased in the cardiac tissue of ADR-treated WT mice compared with control, and this effect was significantly suppressed by dunnione (Fig.…”
Section: Dunnione Inhibits Acetylation Of Nf-κb P65 and Production Ofmentioning
confidence: 86%
“…6E-F). As previously demonstrated, ADR induces the activation of acetylated p53 [29], a key mediator and upstream regulator of miR-34a [28]. Therefore, we assessed whether dunnione reduced ADR-induced acetylation of p53 in the cardiac tissue.…”
Section: Dunnione Reinstates Adr-induced Sirt1 Activity and Protein Ementioning
confidence: 89%
See 1 more Smart Citation